Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 68

Answer

$\dfrac{5x-1}{4x}-\dfrac{3x-2}{4x}=\dfrac{2x+1}{4x}$

Work Step by Step

$\dfrac{5x-1}{4x}-\dfrac{3x-2}{4x}$ Evaluate the substraction and simplify if possible: $\dfrac{5x-1}{4x}-\dfrac{3x-2}{4x}=\dfrac{5x-1-(3x-2)}{4x}=...$ $...=\dfrac{5x-1-3x+2}{4x}=\dfrac{2x+1}{4x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.